Functional Disorders of the Biliary System: Biliary Dyskinesia and Sphincter of Oddi Dysfunction - Mikailla, Romy Healthy; Wulandari, Baiq Nurhandini; Wardana, Shira Putri; Firdaus, Nadine Aisyah Sultan; Ramadhan, Panji Sena; Aghni, Hasna Tazkia; Nurhidayati, Nurhidayati (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Functional biliary disorders are conditions caused by biliary dysmotility without the presence of gallstones, sludge, microlithiasis, or microcrystalline disease. The most common functional biliary disorders are biliary dyskinesia and sphincter of Oddi dysfunction. This study employed a literature review method by searching and reviewing various references from online databases such as PubMed, Google Scholar, and ProQuest. Functional biliary disorders such as biliary dyskinesia and sphincter of Oddi dysfunction often cause biliary pain without gallstones. Although not life-threatening, these disorders can affect quality of life and require appropriate management. Pharmacological treatments such as NSAIDs and ursodeoxycholic acid (UDCA) can help alleviate symptoms of biliary disorders, but surgical interventions such as cholecystectomy and sphincterotomy may be necessary for more severe cases. The choice of treatment method should take into account the risks and complications, and be carried out by an experienced medical team.